Antifungal efficacy of Azadirachta indica (neem) - An in vitro study - Srinidhi Surya Raghavendra; Ketaki Dattatray Balsaraf (Universidade Estadual de Campinas, 2010)
Aim: To evaluate antimicrobial ability of neem leaf extract, 3% sodium hypochlorite (NaOCl) and 2% chlorhexidine (CHX) against Candida albicans. Methods: Neem leaf extract was prepared by using absolute ethanol with fresh neem leaves, filtering the extract through muslin cloth, coarse residue and filter paper. Cultures of C. albicans were maintained on Brain Heart Infusion broth and Agar. The antimicrobial efficacy was checked using the Agar Diffusion and the zones of inhibition were measured. The results were statistically analysed using ANOVA test. Inter-group comparison was checked using Kruskal Wallis ANOVA and Mann Whitney tests (a=0.05). Results: There was statistically significant difference between the zones of inhibition seen with 3% NaOCl and Neem extract with 2% CHX (p<0.05). There was no significant difference observed between Neem extract and 3% NaOCl. Conclusions: Efficacy of Neem extract is comparable to 3% NaOCl against C. albicans and it is significantly better than 2% CHX.